Diagnosis of Tubercular Pleural Effusion in a Tertiary Care Hospital of Western India: Role of Cartridge-based Nucleic Acid Amplification Test and other Laboratory Parameters - Sahjid Mukhida; Sameena Khan; Chanda Vyawahare; Nageswari R. Gandham (Journal of Marine Medical Society)
Introduction: Tubercular pleural effusion (TPE) is a paucibacillary disease, and mycobacterial culture positivity from pleural fluid samples is rare and time-consuming, leading to considerable delay in initiating antibiotic therapy. However, in high-burden settings, the diagnosis is presumed in individuals based on adenosine deaminase (ADA) level and a lymphocytic-predominant exudate on presentation. The current study was conducted to screen clinically TPE-suspected patients by cartridge-based nucleic acid amplification test (CBNAAT) as well as culture and to evaluate whether TPE correlates with pleural fluid laboratory counts. Materials and Methods: This observational study was done at a tertiary care hospital from January 2019 to June 2021 on 157 TPE-suspected patients. CBNAAT was performed for both pleural fluid and sputum specimens while solid culture was processed on pleural fluids only as per routine microbiological procedures. Pleural fluid was sent for biochemical analysis and investigation of ADA, total leukocyte count, and differential leukocyte count because of lymphocyte predominance. Results: A total of 314 specimens (pleural fluid and sputum) from 157 patients were processed for CBNAAT. Mycobacterium tuberculosis was detected in 22 (14.01%) of 157 sputum specimens and 19 (12.10%) of 157 pleural fluid specimens. A total of 25 pleural fluid specimens have growth on solid media. CBNAAT sensitivity was found 52% in the current study. A total of seven patients were detected with pulmonary tuberculosis (PTB) along with TPE. In TPE diagnosis, all laboratory parameters were found statistically significant (P < 0.5). Conclusion: The use of two tests for patient screening, such as the CBNAAT and supporting marker test, improves the early detection of TPE and stops the progression of problems from untreated, long-standing TPE. This study also reveals the significant correlation of PTB in clinically TPE-suspected patients.